Strategi Perencanaan SDM yang Efektif dalam Meningkatkan Kinerja Organisasi - Zulfikar, Zulfikar; Fatimah, Nur; Ikhsan, Ikhsan; Permadi, Rendhy Satriyo; Fadilla, Nur; Dinsar, Arfandy (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
This journal discusses how to improve the performance of large companies through effective Human Resource (HR) plans. The research examined a wide range of companies and found that proactive career planning, skills-focused training, and adaptive performance appraisals can positively affect organizational performance. The results provide practical guidance for large company leaders to optimize HR strategies to improve efficiency and long-term performance